To the Question of Liability for an Inefficient Expenditureof Budgetary Funds - Irina G. Lvova (Сибирское юридическое обозрение)
The article deals with the principle of efficiency of use of budgetary funds. It is emphasized that the responsibility for breaking the budgetary legislation is subject to law is highly controversial and with large gaps that ensure compliance with the principle of efficiency of the use of budgetary funds, which in turn causes the state considerable economic damage. This article analyzes the existing in scientific literature approaches to the concept and content of budget expenditure efficiency, and also examines the problems of legal regulation, the possibility and necessity of inclusion in the legislation establishing liability for an inefficient expenditure of budgetary funds.